Implementation of the Philosophy of Justice in Islamic Economics on Business Competition Supervision - PADLI PADLI (Journal of Economic Perspectives and Business Innovation, 2024)
AbstractThe philosophy of justice in Islamic economics provides a moral and ethical framework for regulating business competition and ensuring fairness in market practices. This study examines how the principles of justice derived from Islamic economic thought can be implemented in the supervision of business competition. Using a qualitative normative approach, the research analyzes classical Islamic economic literature, contemporary regulatory frameworks, and ethical doctrines related to market behavior. The findings suggest that Islamic justice emphasizes balance, transparency, prohibition of exploitation, and protection of public welfare. Effective supervision of business competition, therefore, should not only focus on legal compliance but also incorporate ethical accountability and social responsibility. The integration of Islamic philosophical principles into modern regulatory systems can strengthen fair competition, prevent monopolistic behavior, and promote equitable economic development. The study concludes that justice-oriented supervision is essential for creating a sustainable and socially responsible economic environment. Keywords: Islamic economics, philosophy of justice, business competition, market ethics, economic regulation